THE PATTERN OF LIVING HABITS OF YOUNG WOMEN TOWARDS THE INCIDENCE OF PRIMARY DYSMENORRHEA IN THE CITY OF BENGKULU - Mariati Mariati; Lela Hartini; Yuniarti Yuniarti; Nur Annisa Muslimah (Poltekkes Kemenkes Bengkulu, 2023)
According to the World Health Organization (WHO), 1,769,425 people (90%) were found to suffer from dysmenorrhea (WHO, 2019). In Indonesia, the prevalence of primary dysmenorrhea reaches 54.89% (Pangestu, 2020). In Bengkulu, the prevalence of Dysmenorrhea is 82% (Ministry of Education and Culture of Bengkulu City, 2022). The design used in this research is observational analytic with a cross sectional approach. The population in this study were 7th grade students at SMPN 02 Bengkulu City, totaling 186 students, the largest number of female students compared to other junior high schools. Samples were taken using total sampling for all 7th grade students who experienced dysmenorrhea, and for the rest using random sampling with clusters. This research method uses the Chi-square test and Logistic Regression. The results of the Chi-square test showed that the p-value of knowledge with primary dysmenorrhea was 0.000<0.05, meaning there was a relationship between knowledge and primary dysmenorrhea, fast food consumption with primary dysmenorrhea 0.000<0.05, meaning there was a relationship between fast food consumption and the incidence of primary dysmenorrhea, and exercise habits and the incidence of primary dysmenorrhea 0.000 <0.05 means there is a relationship between the incidence of primary dysmenorrhea. The results of multivariate analysis show that the factor that most influences the incidence of dysmenorrhea is consumption of fast food with a value of p = 0.000; OR: 9.518 (2.972-30.486) meaning that fast food consumption has an influence of 9 times on the incidence of primary dysmenorrhea.